Analisis Kebutuhan Pengembangan Aplikasi Edukasi Pada Masa Nifas - Ni Made Dwi Mahayati; I Gusti Agung Ayu Novya Dewi; Ni Komang Erny Astiti (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
The puerperal period is accompanied by various changes, can be physiological or pathological, that can minimized by providing effective information for mothers. Currently, the dissemination of information is practically through mobile applications. The purpose of this study was to analyze the needs for the development of educational applications for postpartum care. The mixed method research was conducted with respondent was 65 postpartum women and 3 midwives using purposive sampling technique. The research instrument was a questionnaire and an interview guide. Data analysis used univariate and qualitative analysis. The results showed that the use of MCH Handbooks was mostly good (67.69%), educational media were mostly MCH books (44.74%), the most education was exclusive breastfeeding (96.92%), the least education is physical exercise during the postpartum (63.08%). Analysis show that the most needed information is information about exclusive breastfeeding (81.54%) and the need for educational media other than MCH books (84.62%). Qualitative results indicate that online postpartum information media needed by respondents beside the MCH book currently used. Midwives should develop innovative educational media so that higher quality postpartum care can be provided.